2009
DOI: 10.1080/13651500802607683
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the components of sleep quality in medical outpatients

Abstract: Background. Almost any medical illness that causes significant pain or discomfort may negatively affect the quality of sleep. Moreover sleep disorders may coexist with medical disorders in people of all ages. Measuring sleep dysfunction is an area of active research, but few studies examined subjective ratings of sleep quality in medical patients Method. A total of 250 medical patients with various somatic complaints who attended the ENT, internal, neurology, orthopaedics and urology clinics participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…In a study done by Meissner and others [3] insomnia was found in 47% of patients while other researchers have reported a prevalence of 59% [9]. Numerous investigators have demonstrated increased prevalence of insomnia in subjects with somatic diseases [10][11][12]. Restless legs syndrome, a was found in 22.52% of the patients in our study which is higher than that found in normal population.…”
Section: Discussioncontrasting
confidence: 53%
“…In a study done by Meissner and others [3] insomnia was found in 47% of patients while other researchers have reported a prevalence of 59% [9]. Numerous investigators have demonstrated increased prevalence of insomnia in subjects with somatic diseases [10][11][12]. Restless legs syndrome, a was found in 22.52% of the patients in our study which is higher than that found in normal population.…”
Section: Discussioncontrasting
confidence: 53%
“…The construct of sleep quality measured by the PSQI encompasses seven components that form distinct clusters of individuals according to their health/illness status. For example, medical outpatients not only have a higher global score compared to non-clinical samples; they also vary their reports on component scores according to the types of clinics they attend and the nature of the sleep disturbances they present with [33], which can be dependent on varying causes such as medical/physical conditions, sleep disorders, mental/psychological factors, behavioral issues, environmental factors or a combination of any of the above, all of which can impact sleep adversely in different ways, and consequently impact the magnitude of sleep quality through different components. Individuals with obstructive sleep apnea (OSA), one of the most common sleep disorders, are more likely to report shorter sleep onset, longer sleep duration but yet, poorer perceived sleep quality and higher sleep disturbances and daytime dysfunction, compared to healthy controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Poor sleep quality impairs academic performance [2,7] and is associated with an increased risk of psychological morbidity and burnout. [8] Furthermore, irregular sleep schedules, [8] psychoactive substance use, [9] fatigue [10] and co-morbid physical or psychological conditions [11,12] are associated with poor sleep quality. Recent evidence for the predisposing risk of adverse childhood experiences on sleep quality has been reported.…”
Section: Introductionmentioning
confidence: 99%